Karakteristik dan Implikasi Sains Barat Modern Terhadap Lingkungan Hidup - Tanjung, Akbar (Universitas Islam Negeri Raden Intan Lampung, 2019)
Advances in science and technology have made many human activities easier. Such as convenience in transportation, communication, industry, and security. However, it cannot be denied that many negative impacts are also caused by science and technology, including the environment. The problem that originally wanted to be solved by science and technology turned out to be even more complicated. This study will examine how the characteristics and implications of modern Western science on the environment in a Theological review. This research uses the method of abstraction, holistica, and hermeneutical circles. characteristics of modern Western science are based on rationalists, empiricists, and anthropocentric. So that it has bad implications for the environment, the pattern of human interaction with the environment becomes destructive and exploitative of nature.